PENGARUH PENERAPAN SISTEM PENGUMPUL TOL ELEKTRONIK TERHADAP PELAYANAN GERBANG TOL - Sodikin Sodikin; Bambang Pudjianto; Bambang Riyanto (Jurnal Transportasi, 2009)
An Electronic Toll Collection (ETC) system can be used to reduce vehicle queues in toll gates. This study aims to determine the most effective combination of conventional and ETC booths in a toll gate. The Pondok Gede Timur toll gate was selected as a case study for this research. The results show that vehicle flow did not linearly affect the vehicle lost time since the fluctuations of vehicle flows were significantly different from one day to another. The application of ETC system could reduce the queue length, both in conventional and ETC booths located in a toll gate.Keywords: conventional toll booth, ETC booth, lost time, and queue length.